Comparison of aerobic training versus relaxation therapy on anxiety and depression in children with asthma: a pilot study - Gaikwad, Pratibha; Asgoankar, Bharati (International Journal of Research in Medical Sciences, 2025)
Background: Asthma in growing children affects their emotional, intellectual, and physical development. Aerobic training has been advised for asthmatics to increase fitness and cardio-respiratory endurance, decrease dyspnoea, and improve quality of life. However, studies regarding aerobic training and its effect on anxiety and depression in the paediatric population are limited. Psychological treatments can decrease emotional distress as a result of symptoms, but does not improve their physical capacity. Thus, the aim of our study was to study the effects of eight weeks of aerobic training versus Jacobson’s relaxation technique on anxiety and depression in asthmatic children with mild to moderate severity. Methods: It was a single centre prospective comparative study. 45 asthmatic children satisfying the inclusion criteria were screened for anxiety and depression by using revised children's anxiety and depression scale (RCADS) scale. They were divided into 3 groups. Group A received diagrammatic breathing exercises, group B children received aerobic training, and group C received Jacobson’s relaxation. Pre- and post-8-week effects training effects were assessed. Results: Study results showed there was a significant difference between aerobic and relaxation on anxiety score with p value of 0.004. There was no significant difference on depression score between aerobic and relaxation with p value of 0.086. Conclusion: The study results showed that an aerobic training program reduces anxiety and depression levels in asthmatic children aged 6-11 years.